TASAWUF AND MILLENNIAL YOUTH (In the Perspective Suluk Linglung Sunan Kalijaga) - Zarkasi, Fatchullah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2021)
The purpose of this study was to determine the form of moral education according to Sunan Kalijaga in Suluk Daze. This study uses a qualitative method as a literature study, namely data collection aims to analyze Moral Education according to Sunan Kalijaga in Suluk Linglung's work. This research uses In this research process there are several stages carried out, namely by reading, understanding and reviewing books, interpretations, as well as living witnesses of the heirs and caretakers of the Tomb of Kanjeng Sunan Kalijaga and other sources related to the problems which are then analyzed. The results of this study are morals as a medium for receiving divine guidance, morality as a means of obtaining the benefits of knowledge, and morals as the main practice.